2009
DOI: 10.1523/jneurosci.3590-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Pathways Mediate Spine Alterations and Cell Death Induced by Amyloid-β, Wild-Type Tau, and R406W Tau

Abstract: Alzheimer's disease is characterized by synaptic alterations and neurodegeneration. Histopathological hallmarks represent amyloid plaques composed of amyloid-␤ (A␤) and neurofibrillary tangles containing hyperphosphorylated tau. To determine whether synaptic changes and neurodegeneration share common pathways, we established an ex vivo model using organotypic hippocampal slice cultures from amyloid precursor protein transgenic mice combined with virus-mediated expression of EGFP-tagged tau constructs. Confocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
138
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 39 publications
(57 reference statements)
17
138
0
Order By: Relevance
“…(3) Other studies indicate that tau may interfere with signaling pathways, or molecules such as GSK3␤, thereby exerting more indirect control over transport processes. 20,49 Our data support tau-induced anterograde transport deficits as the general mechanism by which mitochondria become improperly distributed. The re-distribution of mitochondria following doxycycline treatment in the rTg4510, even in the continued presence of neuropil threads or NFT, suggests that the presence of aggregates of tau may not, in fact, serve as roadblocks, but rather that soluble tau species interfere with mitochondrial trafficking by some other means.…”
Section: Discussionsupporting
confidence: 63%
“…(3) Other studies indicate that tau may interfere with signaling pathways, or molecules such as GSK3␤, thereby exerting more indirect control over transport processes. 20,49 Our data support tau-induced anterograde transport deficits as the general mechanism by which mitochondria become improperly distributed. The re-distribution of mitochondria following doxycycline treatment in the rTg4510, even in the continued presence of neuropil threads or NFT, suggests that the presence of aggregates of tau may not, in fact, serve as roadblocks, but rather that soluble tau species interfere with mitochondrial trafficking by some other means.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies show that overexpression of human mutant tau proteins impairs synapses (14,34). We found that overexpression of hTau significantly decreased spine density both in hippocampal neurons cultured for 12 d in vitro (div) (Fig.…”
Section: Overexpression Of Htau In Hippocampal Neurons Induces Memorymentioning
confidence: 59%
“…Interestingly, alterations in spine structure and other plasticity-associated changes caused by tau misprocessing [236,237] may well involve the small amount of tau that is normally localized to the postsynaptic region in dendrites, as inducible P301L (rTg4510) mice show transient increases in behavioral plasticity before the onset of P301L tauinduced neurodegeneration [238], a finding that is consistent with the reduced MT binding of P301L tau, which presumably is therefore more likely to associate with perimembranous actin cytoskeleton rather than axonal MT.…”
Section: Whither the Cell Cycle?mentioning
confidence: 81%